Using E-learning to enhance the learning of graph transformations - Lee , Ya Ling (2002)
Graphical representation of functions give more meaning to algebraic expressions and is suited to a particular mathematical task. Most of the distance students in Open University Malaysia (OUM) are unable to graph functions and cannot sufficiently understand graph transformations when taught through printed learning materials. Therefore, e-learning is recommended as an aid to enhance the learning of graph transformations for various types of functions. The objectives of the e-learning are to enable students to: 1) visualize graph transformations, 2) simulate graphical representations and 3) sketch functions with guidance. The e-learning develops in a natural progression from an animated presentation to guided and advanced level exercises. The elements of animation and interactivity create an educationally stimulating environment that can enhance the learning of mathematical issues and discovery of mathematical principles. This e-learning will be tested with the students in OUM to verify its effectiveness in the learning of functions and graph transformations. (Author's abstract)